Adesão a protocolo de atendimento do trauma pediátrico em um centro de trauma brasileiro - Botelho Filho, Fabio Mendes [UNIFESP] (2020)
Objectives: this study aims to quantify the adherence of trauma assessment protocols among different types of frontline trauma providers. As a secondary objective, it was also evaluated if adherence is associated with improved clinical outcomes for children. Methods: A descriptive study of pediatric trauma care in Hospital João XXIII was conducted between October 2017 and March 2018. Trauma primary survey assessments were observed and adherence to each step of a standardized primary assessment protocol was recorded. Adherence to the assessment protocol was compared considering different types of providers, the time of presentation, and severity of injury. The relationship between protocol adherence and clinical outcomes including mortality, length of hospital stay, admission to pediatric intensive care unit, use of blood components, need of mechanical ventilation, and number of imaging exams performed were also assessed. Results: Emergency Department evaluations of 64 patients of 274 pediatric admissions were observed over a period of 6 months. The mean patient age was 7.3 years. 40.6% of patients presented due to fall injuries and a majority sustained injury categorized as severe (59.4%). 50% of the primary assessments were performed by general surgeons, 34.4% by residents in general surgery and 15.6% by pediatricians. There was an average adherence rate of 34.1% to the trauma primary assessment protocol. Adherence among each specific step included airway: 17.2%; Breathing: 59.4%; Circulation: 95.3%; Disability: 28.8%; Exposure: 18.8%. No differences between specialties or time of presentation (day vs night) were observed as an influencer in physical assessment. Therefore, adherence was lower in severe patients than non-severe patients. Patients with a more thorough primary assessment, independent of severity, underwent fewer CT scans (ROC curve area: 0.661; p:0.027). Finally, no other associations between adherence and outcomes were observed. Conclusions: Our study demonstrates that trauma assessment protocol adherence among trauma providers is low for both surgeons and nonsurgeons. Thorough initial assessment reduced the use of CT scans, suggesting that standardized pediatric trauma assessments may be a way to reduce unnecessary radiologic imaging among children. It suggests that a standardized assessment should be encouraged, because it could decrease number of unnecessary radiologic exams in a child patient.